MATHEMATIC TEACHERS’ PERCEPTION TOWARD THE IMPLEMENTATION OF CURRICULUM 2013 - Suharti Suharti; Ulfiani Rahman; Habibah Ulfayana (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2019)
Abstract:This study aimed to find out the mathematic teachers’ perception about the implementation of Curriculum 2013 the tenth grade in one of schools in Makassar. This research was qualitative descriptive research. The subjects of this study were 4 Mathematic teachers of the tenth grade. Data obtained through interviews, observation and documentation. Data analysis was done by reducing data through summarizing all of the result from interview, observation and documentation. Then, the data were presented in the form of narration and conclusion. The results of this study indicated that the Mathematic teachers’ perception toward the implementation of Curriculum 2013 got negative response. This result based on research analysis: First, the teachers described that Curriculum 2013 was complicated because the core competencies assessed the students from all aspects of attitude, knowledge and skills. Second, the teachers had misconceptions about the scientific approach implemented in Curriculum 2013 which was using discovery/inquiry learning or project based learning model however in reality the teachers used STAD model of cooperative learning. In this case, the lack of socialization had an impact on teachers in applying the Curriculum 2013.Abstrak:Penelitian ini bertujuan untuk mengetahui persepsi guru matematika tentang penerapan Kurikulum 2013 kelas sepuluh di salah satu sekolah di Makassar. Penelitian ini adalah penelitian deskriptif kualitatif. Subjek penelitian ini adalah 4 guru Matematika kelas X. Data diperoleh melalui wawancara, observasi dan dokumentasi. Analisis data dilakukan dengan mengurangi data melalui meringkas semua hasil dari wawancara, observasi dan dokumentasi. Kemudian, data disajikan dalam bentuk narasi dan kesimpulan. Hasil penelitian ini menunjukkan bahwa persepsi guru matematika terhadap penerapan Kurikulum 2013 mendapat respon negatif. Hasil ini berdasarkan analisis penelitian: 1) guru menggambarkan bahwa Kurikulum 2013 rumit karena kompetensi inti menilai siswa dari semua aspek sikap, pengetahuan dan keterampilan. 2) guru memiliki kesalahpahaman tentang pendekatan ilmiah yang diterapkan dalam Kurikulum 2013 yang menggunakan pembelajaran penemuan/penyelidikan atau model pembelajaran berbasis proyek namun pada kenyataannya guru menggunakan model pembelajaran kooperatif STAD. Dalam hal ini, kurangnya sosialisasi berdampak pada guru dalam menerapkan Kurikulum 2013.